Dinamika Kekuasaan dalam Komunitas Jazz Yogyakarta 2002-2010 - Sutopo, Oki Rahadianto (Jurnal Ilmu Sosial dan Ilmu Politik, 2010)
Previous studies about jazz in Indonesia tend to generalize and hold a bias against narration from the mainstream, they do not see the different narration from micro scope. Using Yogyakarta jazz community as an entry point, this study shows that jazz community is not a single entity, rather, it involved various identities including educational as well as social background. This paper also indicates contestation among different jazz community in Yogyakarta wich eventually shape the colour of jazz music in the city.